PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN MAHASISWA KULIAH DI SEKOLAH TINGGI TEKNOLOGI KEDIRGANTARAAN (STTKD) YOGYAKARTA - Sutrisno, Erwan (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
Limited capacity in State Universities makes private universities have the same opportunity to be selected for prospective students who are not accommodated in State Universities in continuing their studies. The ability to obtain a large number of students depends on delivery of information from private university (PTS) concerned, through marketing strategy of services implemented by private universities. This also applies to STTKD Yogyakarta. The formulation of the problem in this study is the extent of influence of advertising, sales promotion, personal sales, public relations and direct marketing on student decisions to study at the Yogyakarta Aerospace Technology College (STTKD). This study aims to (1) find out the influence of advertising, sales promotion, personal sales, public relations and direct marketing on student decisions chosen by the Yogyakarta Aerospace Technology College (STTKD) and (2) to find out which factors are most dominant in student decisions. Theory used is theory of Marketing Management related to Consumer Behavior. Primary data collection techniques with questionnaires, supported by interviews. Sample in this study was 95 respondents. Research method used is quantitative descriptive. Type of research conducted is a case study supported by a survey, nature of this study is descriptive research. Data processing uses SPSS version 15 software with descriptive analysis and hypothesis testing using multiple linear regression analysis. Determination coefficient (R2) is 0.64. This shows that independent variables studied were able to explain 64% of the decision students to choose Yogyakarta Aerospace Technology College, while remaining 36% was explained by other independent variables that were not examined. Results showed that marketing promotion mix (advertising, promotion sales, personal sales, public relations and direct marketing) had a significant effect on students 'decision to choose Yogyakarta Aerospace Technology College, and direct marketing factors had most dominant influence on students' decision to choose education at STTKD Yogyakarta.